Efficacy of propolis extract and eye drop solutions to suppress encystation and excystation of Acanthamoeba triangularis WU19001-T4 genotype - Suthinee Sangkanu; Abolghasem Siyadatpanah; Roghayeh Norouzi; Julalak Chuprom; Watcharapong Mitsuwan; Sirirat Surinkaew; Rachasak Boonhok; Alok K. Paul; Tooba Mahboob; Imran Sama-ae; Sonia M. R. Oliveira; Tajudeen O. Jimoh; et al. (PeerJ, 2024)
Background Propolis is a natural resinous product from a variety of plants and combines it with beeswax and salivary enzymes to create bee glue. Its potentials have been employed in the treatment of many diseases and conditions for centuries. This study, therefore, aims to determine the anti-Acanthamoeba properties of the propolis extract, eye drops coupled to some mechanisms such as inhibition of encystation and excystation. Methods The minimum inhibitory concentrations (MICs) of the most active propolis extract were assessed in trophozoites and cysts of Acanthamoeba triangularis (A. triangularis) at 0.256 and 1 mg/mL, respectively. Results Active eye drops inhibited trophozoites and cysts with a MIC value of 100%. At concentrations lower than their MICs values (1/2–1/16 MIC), propolis and eye drops revealed inhibition of encystation. In addition, at 1/2 MIC, both the propolis extract and eye drops showed potential inhibition of excystation. In combined sets of propolis extract and eye drops, they showed slightly increasing inhibition of encystation and excystation. Surprisingly, the MIC of chlorhexidine decreased when combined with the propolis and eye drops. SEM and TEM images displayed morphological changes in A. triangularis treated with combined sets of propolis extract and eye drops. Conclusion From this study, a new combined eye drop solution with propolis extract was found to be helpful in reducing encystation and excystation in A. triangularis. Therefore, this combination is an alternative for the treatment of eye diseases in early stages along with reducing the entry into the cyst stage of Acanthamoeba. The results of this study revealed new anti-Acanthamoeba inhibitors with promising combined alternative therapeutic potential for the treatment of Acanthamoeba keratitis.